Multinational Firms and the Theory of International Trade and Investment - Batra, Raveendra N.; Ramachandran, Rama V. (American Economic Review, 2016)
tinational corporation in the arena of economic activity and political influence, trade theorists have either ignored it or expressed unguarded skepticism at the ability of the conventional trade models to successfully capture and analyze the features of this new phenomenon.' The purpose of this paper is twofold: first, by building upon the contribution by Richard Caves, we will show that the traditional trade models can be adapted in a way that preserves most, if not all, of the attributes introduced by international firms.2 Second, we will conduct a comparative statics analysis to explore the implications of tariffs and taxes for resource allocation and international capital movements. Our results here confirm what has already been well established in myriad empirical studies, that maturation of the international firm has vastly increased economic interdependence among trading countries, and that few nations can eschew the ripples caused by economic policies of other nations.3